The contributions of the textbook to the teaching of Geography (Research, Society and Development, 2020)
The article focuses on raising reflections regarding school education in view of the training of students on the impacts of human activity on nature. It deals with the result of an interview with the geography teacher, and analysis of the textbook, its organization, distribution, theoretical framework, teaching methodology, quantity, quality, objective, understanding of the themes and the evaluation activities. The analyzed geography book is adopted for a second year high school class of the 2019 school year in a state school in the municipality of Juara, Mato Grosso, so the analysis has as objective The objective has the purpose of answering the southeastern question: the contributions of the contents of the geography subject and the didactics used by the teacher in preparing students for life in society and identifying the criticality of the relationship between human and nature. The work was developed through a bibliographic survey, mainly by Vesentini, Buene, Covezi, Crispim, Albano, Delizoicov, among others, and analysis of the Geography book by Silva e Júnior from the second year of high school. Qualitative research contributed to the analysis of the collected data. Nowadays, with the revaluation of geographic knowledge, the school approach to natural resources and physical aspects assumes an important role. This knowledge needs to awaken a critical attitude in students, including behaviors. It is concluded that the methodology of textbooks, when combined with a quality work by the teacher, provide the student to acquire the necessary knowledge to understand nature and society, through a harmonious relationship.